BIOPROCESS OPTIMIZATION AND CHARACTERIZATION OF RECOMBINANT URATE OXIDASE EXPRESSED IN Escherichia coli - MURALI KRISHNA. KALUGONDA; T. C. VENKATESWARULU; RAVIKANTH REDDY KOSANA; CHITRA BAJJJI; VENKAT R. KONDA; ANIL. G; KANUMURI RADHA MADHAVI; RAJESH R. TUMMURU; T. SRIVALLI (International Journal of Pharma and Bio Sciences, 2013)
Tumor Lysis Syndrome and Gout are the conditions in which uric acid levels in the serum will be increased up to 526 mg/dl but in a healthy human being the uric acid concentration is less than 15mg/dl. In such conditions urate oxidase can be administered parentrally which can solublise the uric acid in to allontoin which has 3 to 5 fold more solubility than uric acid and it can be excreted through urine and maintain the uric acid concentration at normal level. In this article urate oxidase gene was isolated Aspergillus flavus and it was cloned in to E.coli (BL-21). Urate oxidase gene was expressed in the cytoplasm as soluble and biologically active form. Bioprocess was optimized for 20lts fermenter scale with modified LB medium and purified up to >96% purity using fractionated ammonium sulphate precipitation, diafiltration, anion exchange chromatography, cation exchange chromatography and gel filtration chromatography. The final yield of purified recombinant urate oxidase from the 20lts fermenter was approximately 5 to 6gm of 96% pure and biologically active enzyme.